An analysis of individual and departmental geographical stories, and their role in sustaining teachers. Issue 2 (2nd April 2016) - Puttick, Steven
ABSTRACT: Teaching can be a hard job, and sustaining teachers throughout their career can be a challenge, facing pressure from performativity, increasing accountability, and increases in teacher workload. Geographical stories offer an important source of inspiration, helping to sustain teachers. Findings are presented from an ethnographic study of secondary school geography departments in England. Every teacher in these departments told compelling stories about their personal histories that have led them to being a geography teacher. The areas of subject specialism they claim are not arbitrary, but are often described through narratives in which events from childhood, schooling, and university are re-told, emphasising their long-standing acquaintance with, and passion for certain geographical issues. Departmental organisational types are discussed, and significant differences between departments are highlighted. Within departments, teachers' individual geographical stories may be re-told to construct collective narratives. These departmental, collective stories position teachers in relation to one another, and offer a further dimension of support for teachers' identity and status. Further research – particularly longitudinal studies – is suggested as one way of developing understandings about the ways in which teachers' individual stories might be re-told in dialogue with the collective stories told by their departments. Implications for initial teacher education include increasing beginning teachers' awareness of the distinctiveness of departments, and tailoring developmental work with them to take more explicit account of the specific contexts in which they are learning to teach.